Latent activity rhythm disturbance sub-groups and longitudinal change in depression symptoms among older men. (26th November 2015) - Smagula, Stephen F.; Boudreau, Robert M.; Stone, Katie; Reynolds, Charles F.; Bromberger, Joyce T.; Ancoli-Israel, Sonia; Dam, Thuy-Tien; Barrett-Connor, Elizabeth; Cauley, Jane A.
Abstract : Activity rhythm disturbances and depression often co-occur among older adults. However, little is known about how activity rhythm disturbances themselves co-occur, or how disturbances to multiple aspects of the activity rhythm relate to depression over time. In this study, we performed a Latent Class Analysis to derive sub-groups of older men [total n  = 2933, mean age = 76.28, standard deviation (SD) = 5.48] who shared similar patterns of activity rhythm disturbances (defined as extreme values of modeled activity rhythm parameters). We found eight sub-groups with distinct combinations of activity rhythm disturbances: one had all normative activity rhythm parameters (32.09%), one had only lower activity (10.06%), three had earlier activity (totaling 26.96%) and three had later activity (totaling 30.89%). Groups with similar timing were distinguished depending on whether the relative length of the active period was shorter and/or if the activity rhythm had lesser amplitude/robustness. We next examined whether the derived activity rhythm sub-groups were associated with different rates of change in depression symptom levels over an average of 5.5 (0.52 SD) follow-up years. The sub-group with lower activity only had faster increases in depressive symptoms over time (compared with the group with normative rhythm parameters), but this association was accounted for by adjustments for concurrently assessed health status covariates. Independent of these covariates, we found that four activity rhythm disturbance sub-groups experienced faster depressive symptom increases (compared with the normative sub-group): These included all three sub-groups that had later activity timing and one sub-group that had earlier activity timing plus a shorter active period and a dampened rhythm. Low activity rhythm height/robustness with normal timing therefore may mark depression risk that is attributable to co-occurring disease processes; in contrast, having late or combined early/compressed/dampened activity rhythms may independently contribute to depression symptom development. Our findings suggest that activity rhythm-related depression risk is heterogeneous, and may be detected when multiple aspects of rhythm timing are delayed or when early timing is accompanied by compressed/dampened activity rhythms. Future studies should consider how distinct combinations of altered activity rhythm timing and height/robustness develop and conjointly determine health risks. Further research is also needed to determine whether/how activity rhythms can be modified to improve depression outcomes.